2022
DOI: 10.3389/fvets.2022.921160
|View full text |Cite
|
Sign up to set email alerts
|

The Development of 3D Bovine Intestinal Organoid Derived Models to Investigate Mycobacterium Avium ssp Paratuberculosis Pathogenesis

Abstract: Mycobacterium avium subspecies paratuberculosis (MAP) is the etiological agent of Johne's Disease, a chronic enteritis of ruminants prevalent across the world. It is estimated that approximately 50% of UK dairy herds are infected with MAP, but this is likely an underestimate of the true prevalence. Infection can result in reduced milk yield, infertility and premature culling of the animal, leading to significant losses to the farming economy and negatively affecting animal welfare. Understanding the initial in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…3D bovine enteroids were prepared as described in Hamilton et al ( 112 ). Infection of organoids was carried out as described by Derricott et al ( 70 ) and Blake et al ( 113 ) with modifications. 3D organoids were mechanically disrupted into multicellular fragments by pipetting to expose the apical surface of the cells in 80% of the enteroids.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3D bovine enteroids were prepared as described in Hamilton et al ( 112 ). Infection of organoids was carried out as described by Derricott et al ( 70 ) and Blake et al ( 113 ) with modifications. 3D organoids were mechanically disrupted into multicellular fragments by pipetting to expose the apical surface of the cells in 80% of the enteroids.…”
Section: Methodsmentioning
confidence: 99%
“…The sheared enteroids were counted using a bright-field microscope and diluted to the final concentration of 2,500 enteroids/well. Each enteroid was estimated to contain approximately 40 cells as described by Blake et al ( 113 ). The sheared enteroids were then diluted to the appropriate concentration with IntestiCult Organoid Growth Medium (STEMCELL Technologies) supplemented with 10 ÎŒM ROCK pathway inhibitor (Cayman chemicals), 10 ÎŒM Galunisertib (Cayman Chemicals), and 10 ÎŒM p38 inhibitor (Enzo) and aliquoted into 15 mL falcon tubes for each condition.…”
Section: Methodsmentioning
confidence: 99%
“…Human intestinal organoids have proven successful for culturing human rotavirus (HuRoV), norovirus, and enteroviruses [ 22 , 25 , 26 ], and porcine enteroids have been used to study infection caused by porcine enteric coronaviruses and the host innate response [ 27 ]. Although studies on bovine enteroids infected with enteric pathogens are limited to date, there are some studies on the characterization of cell types and culture of bovine rotavirus (BRoV) group A, Salmonella typhimurium, Toxoplasma gondii, and Mycobacterium avium subspecies paratuberculosis [ 17 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apical‐out organoids were first published by Co et al, who have demonstrated that human intestinal organoids that usually grow embedded in a three‐dimensional extracellular matrix (ECM) can reverse their polarity when they are cultured in a floating manner in medium without ECM 12 . This method has now been adopted by many other labs and expanded to different animal species, for example, pigs, 13 chickens, 14 cows 15 and dogs, 16 and also organoids derived from human iPSCs and embryonic stem cells 17,18 . Remarkably, regardless of the species from which the organoids were derived, the majority of these studies utilised their apical‐out organoids within the initial 7 days following the induction of polarity reversal 13,16,17,19–21 .…”
Section: Introductionmentioning
confidence: 99%